Project Delay Risk Assessment - Farida Rachmawati; Herdira Dita Ramadhani; Aulia Shofi Nurhidayah (IPTEK The Journal for Technology and Science, 2023)
Maintenance activities on power plant projects, which are located in remote areas, are prone to risks related to project delay due to the high complexity of work and limited completion time. This research aimed to fill the existing research gap by developing a delay risk assessment of those projects using a probability impact matrix, which is then transformed into a fuzzy set theory. A case study has been undertaken to represent this research topic at three PLTMGs in Nusa Tenggara. The research steps were potential delay risks identification, critical risk assessment, and risk response development. The results show that the critical risks are lack of skilled and experienced manpower, delay in material and equipment delivery, poor communication and coordination between the contractor and the client, unavailability of materials in the local market, and incomplete material received. Several risk responses are provided in this research, such as strengthening the qualification of the job vacancy, having regular training or sharing sessions before the project execution, and having a stock of emergency spare parts in the central warehouse.